Implementasi Instruksi Presiden Nomor 1 Tahun 2025 tentang Efisiensi Belanja dalam Pelaksanaan APBN dan APBD serta Dampaknya terhadap Program Prioritas di Dinas Pendidikan dan Kebudayaan Provinsi NTT - Esda Gracia Hina Kanni; Saryono Yohanes; Josef Mario Monteiro (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the implementation of Presidential Instruction Number 1 of 2025 concerning expenditure efficiency in the implementation of the State Budget (APBN) and Regional Budget (APBD) at the Department of Education and Culture of East Nusa Tenggara Province, as well as its impact on priority educational programs. The research employs an empirical legal method with a socio-juridical approach through interviews, observations, and document analysis. The findings indicate that the efficiency policy has been implemented through the establishment of an Expenditure Efficiency Team, administrative service digitalization, procurement consolidation, and the refinement of priority programs. Although the policy has been administratively effective and has generated significant budget savings, its implementation continues to face challenges, including limited digital infrastructure, archipelagic geographical conditions, and human resource capacity constraints. The efficiency measures have also affected several priority programs, particularly school infrastructure rehabilitation, teacher competency development, character education, and local cultural preservation. Therefore, more adaptive and affirmative policies are required to ensure that budget efficiency measures do not undermine the constitutional right of citizens to access quality education.